Carbon-branched delta-tetrahydrofuran sugar amino acids (SAAs) as dipeptide isostere scaffolds - Simone, M; Edwards, A; Tranter, G; Fleet, G (2008)
The synthesis of the first branched sugar amino acid (SAA) scaffolds [methyl (3R,4R,5R)-5-azidomethyl-3,4-dihydroxy-tetrahydrofuran-3-carboxylate and methyl (3R,4R,5S)-5-azidomethyl-3,4-dihydroxy-tetrahydrofuran-3-carboxylate] by an efficient intramolecular displacement of a highly hindered neopentyl triflate allows access to enantiopure THF derivatives which have carbon substituents. © 2008 Elsevier Ltd. All rights reserved.